Gestão de ideias: estrutura de referência para inovação aberta - Stankowitz, Rosângela de Fátima (2014)
Innovation management is a difficult subject to be dealt with, regarding a constant technological product shifting. Nevertheless, it is a surviving and competitive edge condition for companies which, being aware of that, search for innovative ideas. Concept management works as to attract ideas to foment the process. The aim of this research is to propose a referential structure to attract ideas, employing open innovative actions. The theoretical reference is assembled through a bibliometric and systemic research on the subject. A conceptual and empiric structure is also assembled. The aforementioned structure is validated with P&D managers from 12 (twelve) midsize and large size Brazilian industrial companies which manage innovative ideas. The researching instrument addressed four stages: reception, selection, evaluation, and pre-development of the ideas. The aims of the research are tabulated as exploratory and descriptive. The nature of the research is applied, predominantly qualitative, employing field research as a method. The main results have demonstrated that the most employed ideas sources are clients, expo markets, and competition. The main criteria, employed to accomplish the initial filter to bracket[ the ideas gathered in the external environment, are the descriptive quality, similarities, and adhesiveness from the ideas to the company’s scope. The ideas are evaluated according to technical, economical, human, logistic and marketing capability for the development. The most employed evaluation criteria, to approve the ideas, are related to the augment of competitiveness, client benefits, and financial return potential. In the evaluation stage, the ideas are recognized and rewarded with money, commemorative events, external divulging, or in the company’s website. Regarding the pre-development, the companies internalize the new ideas, in tandem with the licensing of outsourced technologies, searching for external working capital to finance its development. The companies develop various open innovative actions professed by the specialized literature. However, the companies do not elaborate a plan of action to cope with the ideas approved for development. Thus, the importance of systematizing the process is highlighted. The referential structure for management of ideas in the open innovation, formulated in this Doctoral thesis, allows one to identify the new innovation opportunities present in scenarios external to the company.